Coal gangue concrete for flexible support and preparation method thereof

CN122916539APending Publication Date: 2026-10-16SHAANXI TONGREN APPLIED MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611067608.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]本申请的主要目的在于提供一种柔模支护用煤矸石混凝土及其制备方法,旨在解决现有的煤矸石混凝土存在坍落度损失大、强度低、收缩性大等技术问题

Benefits of technology

本申请提供了一种柔模支护用煤矸石混凝土及其制备方法,通过特殊的改性处理工艺和优化的配比设计,有效解决了煤矸石混凝土坍落度损失大、强度低、收缩性大的技术问题。本申请可以充分利用煤矸石固体废弃物,实现井下就地取材,降低材料成本,具有显著的经济效益和环境效益。制备的煤矸石混凝土具有良好的工作性、力学性能和耐久性,满足柔模支护的技术要求,在煤矿沿空留巷工程中具有广阔的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916539A_ABST
    Figure CN122916539A_ABST
Patent Text Reader

Abstract

The application discloses a coal gangue concrete for flexible support and a preparation method thereof. The coal gangue concrete is prepared by mixing modified coal gangue coarse aggregate, modified coal gangue fine aggregate, gravel, cementitious material, water and additives, wherein the mass ratio of the modified coal gangue coarse aggregate to the modified coal gangue fine aggregate is 1:(1-2), the mass ratio of the sum of the modified coal gangue coarse aggregate, the gravel and the cementitious material to the modified coal gangue fine aggregate is (2-3):1, the mass ratio of the modified coal gangue coarse aggregate to the gravel is (1-1.5):1, and the mass ratio of the modified coal gangue fine aggregate to the additives is (95-105):1. The application effectively solves the technical problems of large slump loss, low strength and large shrinkage of the coal gangue concrete, the prepared concrete has good workability, mechanical properties and micro-expansion properties, meets the engineering requirements of the flexible support, realizes the resource utilization of the coal gangue waste, and has remarkable economic and environmental benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of building materials technology, and in particular to a coal gangue concrete for flexible formwork support and its preparation method. Background Technology

[0002] Gob-side retention is a core technology in pillarless mining, and flexible formwork concrete is widely used in gob-side retention. By pumping concrete into a flexible formwork, it hardens to form a roadway filling body, and has been successfully applied in many coal mines in China.

[0003] Currently, ordinary concrete is commonly used as the filling material in engineering projects, but the following problems exist: the sand and gravel aggregate required for ordinary concrete usually needs to be transported from a long distance, which involves a huge amount of work; secondly, the cost of ordinary concrete itself and transportation costs combined result in a high overall cost of roadway retention along the goaf, making it uneconomical.

[0004] Coal gangue is a major solid waste generated from coal mining and washing. Its long-term accumulation on the surface occupies land and pollutes the environment. Crushing and processing it to replace ordinary sand and gravel in the preparation of coal gangue concrete offers significant advantages, allowing for local sourcing and utilization underground. However, coal gangue concrete typically suffers from problems such as large slump loss, low strength, and high shrinkage, making it unsuitable for long-distance pumping and effective support. Summary of the Invention

[0005] The main objective of this application is to provide a coal gangue concrete for flexible formwork support and its preparation method, aiming to solve the technical problems of existing coal gangue concrete such as large slump loss, low strength, and large shrinkage.

[0006] To achieve the above objectives, this application provides a coal gangue concrete for flexible formwork support. The coal gangue concrete is prepared by mixing modified coal gangue coarse aggregate, modified coal gangue fine aggregate, crushed stone, cementitious material, water, and additives. The mass ratio of the modified coal gangue coarse aggregate to the modified coal gangue fine aggregate is 1:(1-2), the mass ratio of the sum of the modified coal gangue coarse aggregate, the crushed stone, and the cementitious material to the modified coal gangue fine aggregate is (2-3):1, the mass ratio of the modified coal gangue coarse aggregate to the crushed stone is (1-1.5):1, and the mass ratio of the modified coal gangue fine aggregate to the additives is (95-105):1.

[0007] Optionally, the modified coal gangue coarse aggregate consists of first-size particles with a particle size of 5mm-10mm and second-size particles with a particle size of 10mm-20mm, wherein the proportion of the first-size particles is 30%-40%.

[0008] Optionally, the mass ratio of water to cementitious material is (0.4-0.45):1.

[0009] Optionally, the coal gangue concrete is prepared by mixing 550 parts of modified coal gangue coarse aggregate, 700 parts of modified coal gangue fine aggregate, 550 parts of crushed stone, 450 parts of cementitious material, 7 parts of additives and water.

[0010] Optionally, the additive is prepared by mixing 1 part polycarboxylate superplasticizer, 0.5 parts polyetheramine, 0.1 part air-entraining agent, and 0.1 part retarder.

[0011] Optionally, the cementitious material is prepared by mixing 364 parts of ordinary silicate cement, 50 parts of grade I fly ash, 36 parts of S95 mineral powder, 30 parts of steel slag powder, 1 part of plastic expansion agent, 2 parts of super absorbent resin and 2 parts of nano SiO2.

[0012] Furthermore, in order to achieve the above objectives, this application also provides a method for preparing the above-mentioned flexible formwork support coal gangue concrete, comprising the following steps: Modified coal gangue coarse aggregate is prepared by sequentially washing and drying coal gangue coarse aggregate, soaking it in nano-calcium oxide aqueous solution under sealed conditions, air drying it, and coating it with a mixture of cement and silica fume slurry. Modified coal gangue fine aggregate is prepared by sequentially washing, drying, soaking in water glass aqueous solution containing silane coupling agent, air drying, and drying. A cementitious material is prepared, wherein the cementitious material is composed of ordinary silicate cement, fly ash, mineral powder, steel slag powder, plastic expansion agent, super absorbent resin and nano-SiO2; An additive is prepared, wherein the additive is a mixture of polycarboxylate superplasticizer, polyetheramine, air-entraining agent and retarder; The modified coal gangue coarse aggregate, the modified coal gangue fine aggregate, crushed stone, the cementitious material, and the additives are mixed with water according to the specified ratio to obtain the coal gangue concrete.

[0013] Optionally, the method for preparing the modified coal gangue coarse aggregate includes: The coarse aggregate of coal gangue is washed with water to remove impurities from the surface and cracks of the coarse aggregate of coal gangue, and then dried. A 10% nano-calcium oxide aqueous solution was prepared. The dried coal gangue coarse aggregate was then soaked in the nano-calcium oxide aqueous solution under sealed conditions. After soaking, the aggregate was removed and air-dried. Cement and silica fume are mixed with water in a 1:1 ratio to prepare a slurry. The air-dried coal gangue coarse aggregate is coated with the slurry to obtain the modified coal gangue coarse aggregate.

[0014] Optionally, the method for preparing the modified coal gangue fine aggregate includes: Coal gangue fine aggregate with a fineness modulus of 2.5-3.5 is washed with water to remove organic fine powder, and then dried. Water glass with a modulus of 2.5 and silane coupling agent were mixed with water in a ratio of 10:1 and stirred to prepare an aqueous solution with a concentration of 30%. The dried coal gangue fine aggregate is added to the aqueous solution for soaking. After soaking, it is taken out and air-dried, and then dried to constant weight to obtain the modified coal gangue fine aggregate.

[0015] Optionally, the preparation of the cementitious material includes: mixing 364 parts of ordinary silicate cement, 50 parts of grade I fly ash, 36 parts of S95 mineral powder, 30 parts of steel slag powder, 1 part of plastic expansion agent, 2 parts of super absorbent resin and 2 parts of nano SiO2. The preparation of the additive includes mixing 1 part of polycarboxylate superplasticizer, 0.5 parts of polyetheramine, 0.1 parts of air-entraining agent and 0.1 parts of retarder.

[0016] Compared with the prior art, this application has the following beneficial effects: This application provides a coal gangue concrete for flexible formwork support and its preparation method. Through a special modification process and optimized mix design, it effectively solves the technical problems of large slump loss, low strength, and high shrinkage in coal gangue concrete. This application can make full use of coal gangue solid waste, realize on-site material sourcing underground, reduce material costs, and has significant economic and environmental benefits. The prepared coal gangue concrete has good workability, mechanical properties, and durability, meeting the technical requirements of flexible formwork support, and has broad application prospects in coal mine goaf retention engineering. Attached Figure Description

[0017] Figure 1 This is a flowchart illustrating the method for preparing coal gangue concrete for flexible formwork support in this embodiment of the application. Figure 2 This is a process flow diagram for preparing modified coal gangue coarse aggregate in the embodiments of this application; Figure 3 This is a process flow diagram of the modified coal gangue fine aggregate preparation process in the embodiments of this application; Figure 4 This is a photograph of the coal gangue concrete for flexible formwork support prepared in the embodiments of this application. Figure 5 This is a physical image of the coal gangue concrete test block for flexible mold support prepared in the embodiments of this application. Detailed Implementation

[0018] To enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are merely some, not all, of the embodiments of the present application. All other embodiments obtained by those skilled in the art based on the embodiments of the present application without creative effort should fall within the scope of protection of the present application.

[0019] Example 1 This embodiment provides a coal gangue concrete for flexible formwork support, wherein the coal gangue concrete is prepared by mixing modified coal gangue coarse aggregate, modified coal gangue fine aggregate, crushed stone, cementitious materials, water and additives.

[0020] 1. Raw material composition and proportions (1) Aggregate system This application employs a composite aggregate system of modified coal gangue aggregate and crushed stone, wherein the mass ratio of modified coal gangue coarse aggregate to modified coal gangue fine aggregate is 1:(1-2). This ratio range was determined through extensive experimental optimization. When the coarse-fine aggregate ratio is less than 1:1, the porosity of the concrete increases and the strength decreases; when the ratio is greater than 1:2, the workability of the concrete deteriorates and the slump loss increases. The preferred ratio is 1:1.5, at which point the concrete possesses both good compactness and excellent pumpability.

[0021] The mass ratio of modified coal gangue coarse aggregate, crushed stone, and cementitious materials to modified coal gangue fine aggregate is (2-3):1. This ratio controls the total volume relationship between aggregate and cementitious materials, directly affecting the mechanical and workability properties of concrete. When the ratio is greater than 3:1, there is too much cementitious material, which not only increases costs but may also lead to increased concrete shrinkage; when the ratio is less than 2:1, there is insufficient cementitious material, resulting in reduced concrete strength. The preferred ratio is 2.5:1.

[0022] The mass ratio of modified coal gangue coarse aggregate to crushed stone is (1-1.5):1. By introducing an appropriate amount of crushed stone, the gradation of the coal gangue aggregate can be improved, thereby increasing the density and strength of the concrete. If the proportion of coal gangue coarse aggregate is too high, the overall strength of the concrete may be insufficient due to the low strength of coal gangue itself; if the proportion of crushed stone is too high, the purpose of utilizing coal gangue is lost. The preferred ratio is 1.2:1.

[0023] (2) Cementitious material system The mass ratio of water to cementitious materials should be (0.4-0.45):1, meaning the water-cement ratio should be controlled between 0.4 and 0.45. The water-cement ratio is a key parameter affecting the strength and durability of concrete. If the water-cement ratio is too low (<0.4), the concrete has poor fluidity and is difficult to pump; if the water-cement ratio is too high (>0.45), the concrete strength decreases and shrinkage increases. A water-cement ratio of 0.42 is preferred.

[0024] (3) Amount of additives The mass ratio of modified coal gangue fine aggregate to additives is (95-105):1. This ratio ensures that the additives can play their full role while avoiding the negative effects of excessive use. If the additive ratio is too low, it will not effectively improve the concrete performance; if the ratio is too high, it may lead to abnormal concrete setting time or reduced strength.

[0025] 2. Parametric characteristics of modified coal gangue coarse aggregate Modified coal gangue coarse aggregate consists of particles with a first size of 5mm-10mm and particles with a second size of 10mm-20mm, with the first size particles accounting for 30%-40% and the second size particles accounting for 60%-70%. This continuous gradation design is conducive to forming a compact packing structure, reducing porosity, and improving the density and strength of concrete.

[0026] The proportion of the first-size particles (5-10mm) is controlled at 30%-40% based on the following considerations: when the proportion is less than 30%, the voids between coarse aggregates increase, requiring more fine aggregates and cementitious materials to fill them, thus increasing costs; when the proportion is greater than 40%, the interference effect between aggregates increases, and the fluidity of concrete decreases. The preferred proportion is 35%.

[0027] 3. Specific formulation plan This embodiment provides a preferred formulation, with the following amounts of each component: Modified coal gangue coarse aggregate: 550 parts Modified coal gangue fine aggregate: 700 parts Crushed stone: 550 portions Cementitious material: 450 parts Additives: 7 parts Water: Based on a water-to-binder ratio of 0.42, approximately 189 parts. This formulation satisfies the following relationship: Modified coal gangue coarse aggregate : modified coal gangue fine aggregate = 550 : 700 = 1 : 1.27; (Modified coal gangue coarse aggregate + crushed stone + cementitious materials): Modified coal gangue fine aggregate = (550+550+450):700 = 1550:700 = 2.21:1; Modified coal gangue coarse aggregate: crushed stone = 550:550 = 1:1; Modified coal gangue fine aggregate: additives = 700:7 = 100:1; Water:cementing material = 189:450 = 0.42:1.

[0028] It should be noted that the 450 parts of cementitious material here refers to the total amount of cementitious material added to the concrete system.

[0029] 4. Composition of cementitious materials The cementitious material is prepared by mixing the following components: Ordinary Portland cement: 364 parts Grade I fly ash: 50 parts S95 mineral powder: 36 parts Steel slag powder: 30 parts Plastic expander: 1 part Superabsorbent resin: 2 parts Nano SiO2: 2 parts (1) Cement matrix Ordinary Portland cement, as the main cementing material, was used in a quantity of 364 parts, accounting for 80.9% of the total cementing material. Cement provides the basic strength of concrete, and its quantity ensures that the mechanical properties of the concrete meet the support requirements.

[0030] (2) Mineral admixtures Fly ash: 50 parts of Grade I fly ash, accounting for 11.1% of the total cementitious materials. Fly ash has a ball-bearing effect, which can improve the workability of concrete, reduce heat of hydration, and reduce shrinkage. At the same time, the secondary hydration reaction of fly ash can improve the later-stage strength of concrete.

[0031] S95 mineral powder: The dosage of S95 mineral powder is 36 parts, accounting for 8.0% of the total cementitious materials. S95 mineral powder has the characteristics of high fineness and good activity. It can fill the voids between cement particles, improve the microstructure of concrete, and increase density and durability.

[0032] Steel slag powder: The dosage of steel slag powder is 30 parts, accounting for 6.7% of the total cementitious materials. Steel slag powder contains certain cementitious active ingredients and can partially replace cement. At the same time, the micro-expansion characteristics of steel slag powder help to compensate for concrete shrinkage.

[0033] (3) Functional additives Plastic expansion agent: 1 part, accounting for 0.22% of the total cementitious material. The plastic expansion agent produces a small amount of expansion during the plastic stage of concrete, which can effectively compensate for plastic shrinkage and reduce the risk of cracking.

[0034] Superabsorbent polymer (SAP): 2 parts, accounting for 0.44% of the total cementitious materials. SAP acts as an internal curing agent in concrete, releasing stored moisture when moisture is insufficient, promoting cement hydration, and reducing autogenous shrinkage and drying shrinkage.

[0035] Nano SiO2: 2 parts, accounting for 0.44% of the total cementitious materials. Nano SiO2 has extremely high specific surface area and activity, which can accelerate cement hydration, fill nanoscale pores, and significantly improve the early strength and durability of concrete.

[0036] 5. Composition of additives The additive is prepared by mixing the following components: Polycarboxylate superplasticizer: 1 part Polyetheramine: 0.5 parts Air-entraining agent: 0.1 parts Retarder: 0.1 parts (1) Polycarboxylate superplasticizer Polycarboxylate superplasticizer is a highly efficient water-reducing agent that disperses cement particles through electrostatic repulsion and steric hindrance, significantly reducing the water consumption of concrete and improving its fluidity and strength. In this invention, the amount of polycarboxylate superplasticizer is 1 part, accounting for 58.8% of the total additives.

[0037] (2) Polyetheramine The amount of polyetheramine used is 0.5 parts, accounting for 29.4% of the total additives. Polyetheramine is a special organic amine compound that plays multiple roles in this invention: firstly, as a clay hydration inhibitor, it inhibits the infiltration hydration of clay minerals in coal gangue, reducing the fluidity of concrete; secondly, while ensuring good concrete fluidity, it reduces defects in the formed concrete matrix, thereby improving the strength of concrete.

[0038] (3) Entraining agent The air-entraining agent is used at a dosage of 0.1 parts, accounting for 5.9% of the total additives. The air-entraining agent introduces tiny, uniform, and stable air bubbles into the concrete, improving the concrete's freeze-thaw resistance, while also increasing its fluidity and reducing pumping resistance.

[0039] (4) Retarder The retarder dosage is 0.1 parts, accounting for 5.9% of the total additives. The retarder prolongs the setting time of concrete, prevents setting during long-distance pumping, and ensures smooth construction.

[0040] Example 2 like Figure 1 As shown, this embodiment provides a method for preparing the above-mentioned flexible formwork support coal gangue concrete, including the following steps: Step 1: Prepare modified coal gangue coarse aggregate, such as... Figure 2 As shown; (1) Raw material pretreatment Coal gangue coarse aggregate is washed with water to remove impurities from its surface and cracks, and then dried. Washing removes dirt, dust, and other impurities from the coal gangue surface, which can affect the interfacial bonding between the aggregate and cement paste. The drying temperature is controlled at 105±5℃, and drying is carried out to constant weight to ensure the aggregate is in a dry state, which is beneficial for subsequent processing.

[0041] (2) Soaking in nano calcium oxide solution A 10% aqueous solution of nano-calcium oxide was prepared. Nano-calcium oxide has an extremely high specific surface area and activity, enabling it to penetrate into the microcracks and pores of coal gangue aggregate, react with the active components in the coal gangue, generate cementitious products, and strengthen the aggregate structure.

[0042] The dried coal gangue coarse aggregate was soaked in a nano-calcium oxide aqueous solution under sealed conditions. The sealed conditions prevent carbonization and ensure the activity of the nano-calcium oxide. The soaking time was controlled at 4 hours to ensure full penetration of the nano-calcium oxide. After soaking, the aggregate was removed and air-dried. During the air-drying process, the nano-calcium oxide continued to react with the aggregate, forming a reinforcing layer.

[0043] (3) Grating treatment Cement and silica fume were mixed with water in a 1:1 ratio to prepare a slurry. The combination of cement and silica fume exhibits good binding and activity, forming a dense protective layer on the aggregate surface. The water-to-solid ratio of the slurry was controlled at 0.3-0.4 to ensure appropriate fluidity and adhesion.

[0044] The air-dried coarse coal gangue aggregate is coated with slurry. A roller coating machine can be used to ensure that the aggregate surface is evenly coated with a layer of slurry. After coating, the aggregate is cured at a temperature of 20±2℃ and a relative humidity of ≥95% for 7 days to allow the slurry to fully hydrate and harden, forming a high-strength, dense modified layer.

[0045] Technical principle analysis: The modification treatment of coal gangue coarse aggregate is based on the following principles: Strengthening effect: Nano-calcium oxide penetrates into the aggregate and reacts with active SiO2 and Al2O3 in coal gangue to generate cementitious products such as hydrated calcium silicate and hydrated calcium aluminate, which fill the pores inside the aggregate and improve the aggregate strength.

[0046] Interface improvement: The grouting treatment forms a dense cement-silica layer on the surface of the aggregate. This layer is tightly bonded to the aggregate, improving the interface transition zone between the aggregate and the cement paste, and increasing the overall strength of the concrete.

[0047] Water absorption control: The modified layer reduces the water absorption rate of the aggregate, thereby reducing the absorption of water from the concrete mix and helping to control slump loss.

[0048] Step 2: Prepare modified coal gangue fine aggregate, such as... Figure 3 As shown; (1) Raw material pretreatment Fine aggregates of coal gangue with a fineness modulus of 2.5-3.5 are washed with water to remove organic fine powder, and then dried. Fineness modulus control ensures a reasonable gradation of the fine aggregates, and the removal of organic fine powder avoids its adverse effects on concrete performance. Drying conditions are the same as for coarse aggregates.

[0049] (2) Water glass-silane coupling agent solution treatment A 30% aqueous solution was prepared by mixing water glass (modulus 2.5) and a silane coupling agent in a 10:1 ratio with water and stirring. Water glass (sodium silicate) is a water-soluble silicate that synergistically works with the silane coupling agent to improve aggregate surface properties. The silane coupling agent is an organosilicon compound that effectively reduces the water absorption rate of coal gangue aggregate.

[0050] The dried coal gangue fine aggregate was soaked in an aqueous solution for 4 hours. During the soaking process, water glass penetrated into the aggregate pores and reacted with the aggregate components to generate cementitious products; the silane coupling agent formed an organic film on the aggregate surface, improving the compatibility between the aggregate and the cement paste.

[0051] After soaking, the aggregates are removed and air-dried, then oven-dried to constant weight at a temperature of 105±5℃. The silane coupling agent cures to form a hydrophobic film, reducing the water absorption rate of the aggregates.

[0052] Technical principle analysis: The modification treatment of coal gangue fine aggregate is based on the following principles: Inorganic strengthening: Water glass reacts with the active ingredients in the aggregate to form calcium silicate gel, which fills the pores of the aggregate and improves the strength and hardness of the aggregate.

[0053] Organic modification: Silane coupling agents form a hydrophobic film on the aggregate surface, reducing the water absorption rate of the aggregate and reducing slump loss; at the same time, they improve the interfacial bonding between the aggregate and the cement paste.

[0054] Synergistic effect: The inorganic strengthening of water glass and the organic modification of silane coupling agent produce a synergistic effect, which not only improves the aggregate strength but also improves the interfacial properties, significantly enhancing the overall performance of concrete.

[0055] Step 3: Preparation of cementitious materials 364 parts of ordinary silicate cement, 50 parts of grade I fly ash, 36 parts of S95 mineral powder, 30 parts of steel slag powder, 1 part of plastic expansion agent, 2 parts of super absorbent resin and 2 parts of nano SiO2 were mixed.

[0056] Use a forced mixer to mix for 3-5 minutes to ensure all components are thoroughly mixed. The mixed gelling material should be stored in a sealed container to prevent moisture absorption.

[0057] Mechanism of action of cementitious materials: Multi-component cementitious system: Cement, fly ash, mineral powder and steel slag powder form a multi-component cementitious system. Each component promotes each other during the hydration process, forming a dense hydration product structure.

[0058] Micro-expansion compensation: Steel slag powder and plastic expansion agent provide micro-expansion to compensate for concrete shrinkage and reduce the risk of cracking.

[0059] Internal curing function: The superabsorbent resin absorbs the mixing water and releases moisture during the cement hydration process, thus playing an internal curing role and reducing autogenous shrinkage.

[0060] Nano-reinforcement: Nano-SiO2 fills nanoscale voids, accelerates cement hydration, and improves early strength and density.

[0061] Step 4: Preparation of additives Mix 1 part polycarboxylate superplasticizer, 0.5 parts polyetheramine, 0.1 part air-entraining agent and 0.1 part retarder.

[0062] When mixing, first mix the polycarboxylate superplasticizer and polyetheramine, stir evenly, then add the air-entraining agent and retarder, and finally dilute with water to the appropriate concentration. Additives should be prepared and used immediately to avoid performance degradation due to prolonged storage.

[0063] Synergistic effect of additives: Rheology control: Polycarboxylate superplasticizer provides high fluidity, while polyetheramine reduces the hydration of clay minerals and the adsorption of superplasticizer by coal gangue. The combination of the two makes the concrete have both good fluidity and is not prone to segregation and bleeding.

[0064] Air entrainment and retarding: Air-entraining agents introduce micro-bubbles, improving frost resistance and flowability; retarder extends setting time, ensuring pumpable application. The combination of these two ensures that the concrete maintains good workability while allowing sufficient construction time.

[0065] Step 5: Concrete Preparation Modified coal gangue coarse aggregate, modified coal gangue fine aggregate, crushed stone, cementitious materials, and additives are mixed with water according to the specified proportions to obtain coal gangue concrete.

[0066] Mixing process: Dry mixing: First, put the modified coal gangue coarse aggregate, modified coal gangue fine aggregate, and crushed stone into the mixer and dry mix for 30 seconds to make the aggregates evenly mixed.

[0067] Add cementitious material: Add cementitious material and dry mix for 60 seconds to make the cementitious material evenly coat the aggregate.

[0068] Add water and additives: Add a mixed solution of water and additives, stir for 2-3 minutes until the concrete is uniform.

[0069] The actual image of the coal gangue concrete for flexible formwork support prepared in this embodiment is shown below. Figure 4 As shown, Figure 5 The coal gangue concrete test block for flexible formwork support was prepared.

[0070] Example 3 To verify the effectiveness of the technical solution of the present invention, the performance of the coal gangue concrete for flexible formwork support prepared in Example 1 was tested and compared with that of unmodified coal gangue concrete.

[0071] 1. Test Protocol (1) Experimental proportions Comparative Group 1 (Unmodified Coal Gangue Concrete): Cementitious material 450kg / m³, fine coal gangue aggregate 750kg / m³, coarse coal gangue aggregate 550kg / m³, crushed stone 550kg / m³, water 180kg / m³, water-reducing agent 4kg / m³.

[0072] Experimental group (this application): using the formulation and modification process of Example 1.

[0073] (2) Test items Slump and slump loss (after standing for 1 hour) Compressive strength (3 days, 7 days, 28 days) Shrinkage rate (3 days, 7 days, 28 days, 60 days) 2. Experimental Results (1) The working performance is shown in Table 1. Table 1

[0074] Test results show that the coal gangue concrete provided in this application has excellent workability. The initial slump reaches 215 mm, 19% higher than that of unmodified coal gangue concrete. The slump loss after 1 hour is only 25 mm, far less than the 80 mm of unmodified coal gangue concrete, indicating that the modification treatment significantly improves the slump retention performance of the concrete. The spread reaches 510 mm, indicating that the concrete has good fluidity and filling capacity.

[0075] (2) Mechanical properties are shown in Table 2. Table 2

[0076] The test results show that the compressive strength of the coal gangue concrete provided in this application is higher than that of the unmodified coal gangue concrete at all ages. The 28-day compressive strength reaches 37.4 MPa, which is 21.4% higher than that of the unmodified coal gangue concrete. This indicates that the modified and optimized cementitious material system significantly improves the strength of the concrete.

[0077] (3) Shrinkage properties are shown in Table 3. Table 3

[0078] Test results show that the coal gangue concrete provided in this application has significant micro-expansion properties. The 60-day shrinkage rate is only 510×10⁻⁶. -6 The water absorption rate was 23.9% lower than that of unmodified coal gangue concrete. This indicates that the modified coal gangue reduced the water absorption rate, thereby reducing the self-drying shrinkage inside the concrete. The synergistic effect of the plastic expansion agent, superabsorbent resin, and steel slag powder effectively compensated for the concrete shrinkage and improved the stability of the support structure.

[0079] 3. Results Analysis Based on the above performance tests and comparative analysis, the following conclusions can be drawn: (1) The modification treatment has a significant effect. After modification with nano-calcium oxide and water glass-silane coupling agent, the surface properties and internal structure of coal gangue aggregate are significantly improved. The modified layer reduces the water absorption rate of the aggregate, reduces slump loss, strengthens the aggregate strength, improves the overall strength of concrete, and improves interfacial bonding, enhancing the compactness of concrete.

[0080] (2) Optimization of cementitious material system The multi-component cementitious material system fully leverages the characteristics of each component: cement provides basic strength, fly ash improves workability, mineral powder increases density and later-stage strength, steel slag powder provides micro-expansion, and nano-SiO2 accelerates hydration. The synergistic effect of these components gives the concrete excellent mechanical properties and durability.

[0081] (3) The additive formula is reasonable. The combination of polycarboxylate superplasticizer, polyetheramine, air-entraining agent, and retarder enables precise control of rheology, setting time, and air content. The concrete exhibits both good fluidity and sufficient cohesiveness, meeting the requirements for long-distance pumping.

[0082] (4) Excellent micro-expansion performance The synergistic effect of plastic expansion agent, superabsorbent resin and steel slag powder causes the concrete to produce appropriate micro-expansion, effectively compensating for shrinkage, reducing the risk of cracking and improving the long-term stability of the support structure.

[0083] Example 4 This embodiment analyzes the optimization of key process parameters.

[0084] 1. Concentration of nano-calcium oxide solution (1) Concentration selection The concentration of the nano-calcium oxide solution affects the modification effect. If the concentration is too low (<5%), the modification effect is insufficient; if the concentration is too high (>15%), the nano-calcium oxide cannot react completely, resulting in waste. The optimal concentration is 10%.

[0085] (2) Performance impact is shown in Table 6. Table 6

[0086] Experiments show that at a concentration of 10%, performance is significantly improved while the cost is reasonable.

[0087] 3. Concentration of water glass solution (1) Concentration optimization The concentration of water glass solution affects the modification effect of fine aggregates. Too low a concentration (<20%) results in insufficient modification; too high a concentration (>40%) leads to high solution viscosity and difficulty in penetration. The optimal concentration is 30%.

[0088] (2) Performance impact is shown in Table 7. Table 7

[0089] Experiments show that a concentration of 30% yields the best overall results.

[0090] 4. Water-to-binder ratio (1) Water-to-binder ratio range The water-cement ratio is a key parameter affecting concrete performance. A water-cement ratio that is too low (<0.4) results in poor flowability and difficulty in pumping; a water-cement ratio that is too high (>0.45) leads to reduced strength and increased shrinkage. The optimal range is 0.4-0.45, with 0.42 being preferred.

[0091] (2) Performance impact is shown in Table 8. Table 8

[0092] Experiments show that a water-cement ratio of 0.42 achieves the best balance between workability and mechanical properties.

[0093] Example 5 This application adopts a composite aggregate system of modified coal gangue aggregate and crushed stone. In order to intuitively quantify the improvement effect of the modification process of this application on the water absorption, mechanical and compaction properties of the aggregate, this embodiment simultaneously tests the three core physicochemical indicators of coarse and fine coal gangue aggregate before and after modification: water absorption rate, crushing value and apparent density. The measured data are summarized in Table 9.

[0094] Table 9 Parameters of Coal Gangue Aggregate

[0095] As shown in Table 9, after the complete modification process of this application, the water absorption rate of coarse and fine coal gangue aggregates decreased significantly, which can significantly reduce the rapid loss of slump caused by aggregate adsorption of mixing water during the mixing stage; the aggregate crushing value decreased simultaneously, indicating that the aggregate skeleton strength was improved; the apparent density increased significantly, indicating that the internal pores of the aggregate were fully filled by the modified cementitious products, the overall density of the aggregate was improved, and the workability and mechanical properties of concrete were improved simultaneously from the source of aggregate.

[0096] In summary, this application provides a coal gangue concrete for flexible formwork support and its preparation method. Through a special modification process and optimized mix design, it effectively solves the technical problems of large slump loss, low strength, and high shrinkage in coal gangue concrete. This application can fully utilize coal gangue solid waste, achieving on-site material sourcing underground, reducing material costs, and has significant economic and environmental benefits. The prepared coal gangue concrete has good workability, mechanical properties, and durability, meeting the technical requirements of flexible formwork support, and has broad application prospects in coal mine goaf retention engineering.

[0097] The above are merely preferred embodiments of this application and do not limit the patent scope of this application. Any equivalent structural or procedural transformations made using the content of this application's specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of this application.

Claims

1. A type of coal gangue concrete for flexible formwork support, characterized in that, The coal gangue concrete is prepared by mixing modified coal gangue coarse aggregate, modified coal gangue fine aggregate, crushed stone, cementitious material, water and additives. The mass ratio of the modified coal gangue coarse aggregate to the modified coal gangue fine aggregate is 1:(1-2), the mass ratio of the sum of the modified coal gangue coarse aggregate, the crushed stone and the cementitious material to the modified coal gangue fine aggregate is (2-3):1, the mass ratio of the modified coal gangue coarse aggregate to the crushed stone is (1-1.5):1, and the mass ratio of the modified coal gangue fine aggregate to the additives is (95-105):

1.

2. The coal gangue concrete for flexible formwork support as described in claim 1, characterized in that, The modified coal gangue coarse aggregate consists of first-size particles with a particle size of 5mm-10mm and second-size particles with a particle size of 10mm-20mm, with the first-size particles accounting for 30%-40%.

3. The coal gangue concrete for flexible formwork support as described in claim 1, characterized in that, The mass ratio of water to the cementitious material is (0.4-0.45):

1.

4. The coal gangue concrete for flexible formwork support as described in claim 1, characterized in that, The coal gangue concrete is prepared by mixing 550 parts of modified coal gangue coarse aggregate, 700 parts of modified coal gangue fine aggregate, 550 parts of crushed stone, 450 parts of cementitious material, 7 parts of additives and water.

5. The coal gangue concrete for flexible formwork support as described in any one of claims 1-4, characterized in that, The additive is prepared by mixing 1 part polycarboxylate superplasticizer, 0.5 parts polyetheramine, 0.1 part air-entraining agent, and 0.1 part retarder.

6. The coal gangue concrete for flexible formwork support as described in claim 5, characterized in that, The cementitious material is prepared by mixing 364 parts of ordinary silicate cement, 50 parts of grade I fly ash, 36 parts of S95 mineral powder, 30 parts of steel slag powder, 1 part of plastic expansion agent, 2 parts of super absorbent resin and 2 parts of nano SiO2.

7. A method for preparing coal gangue concrete for flexible formwork support as described in any one of claims 1-6, characterized in that, Includes the following steps: Modified coal gangue coarse aggregate is prepared by sequentially washing and drying coal gangue coarse aggregate, soaking it in nano-calcium oxide aqueous solution under sealed conditions, air drying it, and coating it with a mixture of cement and silica fume slurry. Modified coal gangue fine aggregate is prepared by sequentially washing, drying, soaking in water glass aqueous solution containing silane coupling agent, air drying, and drying. A cementitious material is prepared, wherein the cementitious material is composed of ordinary silicate cement, fly ash, mineral powder, steel slag powder, plastic expansion agent, super absorbent resin and nano-SiO2; An additive is prepared, wherein the additive is a mixture of polycarboxylate superplasticizer, polyetheramine, air-entraining agent and retarder; The modified coal gangue coarse aggregate, the modified coal gangue fine aggregate, crushed stone, the cementitious material, and the additives are mixed with water according to the specified ratio to obtain the coal gangue concrete.

8. The method for preparing coal gangue concrete for flexible formwork support as described in claim 7, characterized in that, The method for preparing the modified coal gangue coarse aggregate includes: The coarse aggregate of coal gangue is washed with water to remove impurities from the surface and cracks of the coarse aggregate of coal gangue, and then dried. A 10% nano-calcium oxide aqueous solution was prepared. The dried coal gangue coarse aggregate was then soaked in the nano-calcium oxide aqueous solution under sealed conditions. After soaking, the aggregate was removed and air-dried. Cement and silica fume are mixed with water in a 1:1 ratio to prepare a slurry. The air-dried coal gangue coarse aggregate is coated with the slurry to obtain the modified coal gangue coarse aggregate.

9. The method for preparing coal gangue concrete for flexible formwork support as described in claim 7, characterized in that, The method for preparing the modified coal gangue fine aggregate includes: Coal gangue fine aggregate with a fineness modulus of 2.5-3.5 is washed with water to remove organic fine powder, and then dried. Water glass with a modulus of 2.5 and silane coupling agent were mixed with water in a ratio of 10:1 and stirred to prepare an aqueous solution with a concentration of 30%. The dried coal gangue fine aggregate is added to the aqueous solution for soaking. After soaking, it is taken out and air-dried, and then dried to constant weight to obtain the modified coal gangue fine aggregate.

10. The method for preparing coal gangue concrete for flexible formwork support as described in claim 7, characterized in that, The preparation of the cementitious material includes: mixing 364 parts of ordinary silicate cement, 50 parts of grade I fly ash, 36 parts of S95 mineral powder, 30 parts of steel slag powder, 1 part of plastic expansion agent, 2 parts of super absorbent resin and 2 parts of nano SiO2. The preparation of the additive includes mixing 1 part of polycarboxylate superplasticizer, 0.5 parts of polyetheramine, 0.1 parts of air-entraining agent and 0.1 parts of retarder.